Pengaruh Model Pembelajaran Problem Solving Terhadap Aktivitas dan Hasil Belajar Matematika Siswa SMP - Kartini Kartini; Nyoman Sridana; Muh. Turmuzi; Baidowi Baidowi (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study was aimed to know the influence of problem-solving learning model to word the activities and results of mathematics learning in the eighth grade of MTsN 2 Dompu in the academic year 2020/2021. This research is an experimental study with a quasi-experimental posttest control group design. The research sample is class VIII-A (experimental class) using a problem-solving learning model and VIII-B (control class) using a direct learning model. The instruments were used for teacher and student activity observation sheets, and student learning outcomes test (posttest) on the material relation and functions. The results showed: 1) the activity of teachers in the experimental class and control was able to reach the very active category. 2) the activity of students in the experimental class was able to reach the very active category while the control class was in the less active category. 3) data analysis using t-test with the value of count = 1,7215 >table= 1,1625 so that H0 was rejected. 4) the average post-test value was greater than the control class. The result of this research showed that problem-solving learning models were influenced toward the result of mathematics learning on the material relations and function at eighth-grade students of MTsN 2 Dompu in the academic year 2020/2021